Online SKCK Service Innovation at Sidoarjo Police: Inovasi Pelayanan SKCK Online di Polsek Sidoarjo - Makhnunah, Ainul; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2021)
The SKCK Online service is an IT-based service at the Police Agency. This Online SKCK service can improve public services, but there are several problems related to this online SKCK service, namely the lack of socialization on how to use it, for SKCK payments only in collaboration with one bank, the lack of facilities and infrastructure. This study aims to describe or describe the process of innovation in SKCK Online services at the Sidoarjo Police Sector and to provide convenience for the community in managing SKCK. This research method uses descriptive qualitative research methods. The technique of collecting data in this study used observation techniques, interview techniques, documentation and the technique of determining the informants used purposive sampling technique. The data analysis technique uses data collection techniques, data reduction, data presentation, and drawing conclusions. The results show that SKCK service innovation is seen from the analysis using the innovation attribute theory according to Rogers, namely: 1. Relative advantage, this aspect provides convenience for the public in accessing and view information and make SKCK, 2. Compatibility, there is a match between high community mobility and technological advances in creating online services, 3. Complexcity, there are still many people who do not know the service and use of online SKCK 4. Triability, this application has gone through a test process because it used to take 3-4 days, now it only takes 10 minutes, and 5. Observability, the online SKCK application helps the community in managing SKCK online and quickly.